Posaconazole inhibits the stemness of cancer stem-like cells by inducing autophagy and suppressing the Wnt/β-catenin/survivin signaling pathway in glioblastoma - Wang, Hua; Tan, Yinfeng; Jia, Hao; Liu, Danqi; Liu, Rangru (Frontiers in Pharmacology, 2022)
Posaconazole (POS) has been reported to present potential antitumor activity for glioblastoma (GBM). However, its molecular mechanisms remain unclear. In this study, we found that POS has potent cytotoxicity and inhibits cell viability and proliferation in GBM. In addition, we adopted a sphere formation assay to detect the self-renewal capacity, performed western blotting to measure cancer stem-like cells (CSC) marker proteins (CD133, SOX2, Nanog and Oct4) and applied flow cytometry to monitor the subpopulation of CD144+/CD33+cells, and the results all demonstrated that POS can remarkably weaken CSC stemness. Furthermore, western blotting, immunoflurescence, transmission electron microscopy and acridine orange staining were performed to detect autophagy-related proteins (LC3, SQSTM1, Beclin 1 and Atg5), count the numbers of endogenous LC3 puncta, visually observe the ultrastructural morphology of autophagosomes and judge the formation of acidicvesicular organelles, respectively, and the results validated that POS promotes autophagy induction. Importantly, the suppressive effect of POS on CSC stemness was partially relieved when autophagy was blocked by the autophagy inhibitor chloroquine (CQ) or Atg5 shRNA. Bioinformatic techniques, including weighted gene coexpression network analysis (WGCNA), gene set difference analysis (GSVA) and KEGG pathway analysis, combined with experimental validations showed that survivin, which is implicated in both autophagy and the stem cell index, is one of the target proteins of POS and that POS weakens CSC stemness via suppressing the Wnt/β-catenin signaling pathway in GBM. Finally, the antitumor activity of POS was confirmed in GBM xenograft models in vivo. Consistent with the in vitro conclusions, POS upregulated the expression of LC3 and decreased the expression of CD133, survivin and β-catenin, as shown by the immunohistochemistry analysis. In summary, this work provides an experimental foundation for exploiting POS as a CSC-targeting antitumor drug for GBM treatment.